2003
DOI: 10.1007/3-540-45851-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Crystal Growth Rate and Its Corresponding State in Polymeric Materials

Abstract: Abstract. The temperature dependence of crystal growth rate (G) shows a bell shape with the maximum growth rate G max. The activation energy for the molecular transport in G could be expressed in terms of equation of either Arrhenius or WLF. The G max showed remarkable molecular weight dependence. The plots of G/Gmax against T /Tcmax showed a single master curve without molecular weight dependence. The ratio of Go/Gmax gave a constant value for each polymer. Plots of ln(G/Gmax)/ ln(Go/Gmax) against T /Tcmax fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Similar trends of polymers with medium molecular weight having the highest crystallization rates is well known in the measurement of crystallization rates of many polymers, such as polyethylene, poly(ethylene oxide), poly(3,3‐diethyl oxetane), PCL and poly(ethylene succinate) . In general, higher molecular weights lead to slower crystallization rates because of the chain entanglement effect, but this trend reverses at lower molecular weights when the melting point effect becomes dominant.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Similar trends of polymers with medium molecular weight having the highest crystallization rates is well known in the measurement of crystallization rates of many polymers, such as polyethylene, poly(ethylene oxide), poly(3,3‐diethyl oxetane), PCL and poly(ethylene succinate) . In general, higher molecular weights lead to slower crystallization rates because of the chain entanglement effect, but this trend reverses at lower molecular weights when the melting point effect becomes dominant.…”
Section: Resultssupporting
confidence: 67%
“…Okui and Umemoto have proposed that for low molecular weight chains intermolecular crystal nucleation dominates crystal growth kinetics, while intramolecular crystal nucleation prevails for high molecular weight chains. 43 Note that the free energy barrier associated with intramolecular crystal nucleation has been found to be independent of chain length. 44 Certainly, such an independence does not occur any more for intermolecular crystal nucleation at low molecular weights.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34] In addition, it was reported that the chains with lower M n prefer extended chain crystallization (ECC) while chains with higher M n prefer folded chain crystallization. 35,36 Considering the alternate arrangement of PLLA and PDLA chains in the lattice, SC is a typical example of intermolecular crystal nucleation and growth; 24 meanwhile, SC prefers the ECC model even with higher M n . Thus, for the PLA samples with higher M n , PLLA adopts the ECC model to a larger extent than the PLLA/PDLA blends.…”
Section: Resultsmentioning
confidence: 99%